Metagenomic analyses reveal previously unrecognized variation in the diets of sympatric Old World monkey species. - Martha M Lyke; Anthony Di Fiore; Noah Fierer; Anne A Madden; Joanna E Lambert (PLoS ONE, 2019)
Insectivory, or the consumption of insects and other arthropods, is a significant yet cryptic component of omnivorous primate diets. Here, we used high-throughput DNA sequencing to identify arthropods from fecal DNA and assess variation in insectivory by closely-related sympatric primates. We identified arthropod prey taxa and tested the hypothesis that variation in insectivory facilitates niche differentiation and coexistence among closely-related species with high dietary overlap. We collected 233 fecal samples from redtail (Cercopithecus ascanius; n = 118) and blue monkeys (C. mitis; n = 115) and used a CO1 metabarcoding approach to identify arthropod DNA in each fecal sample. Arthropod DNA was detected in 99% of samples (N = 223 samples), and a total of 68 families (15 orders) were identified. Redtails consumed arthropods from 54 families, of which 12 (21.8%) were absent from blue monkey samples. Blue monkeys consumed arthropods from 56 families, of which 14 (24.6%) were absent from redtail samples. For both species, >97% of taxa present belonged to four orders (Araneae, Diptera, Hymenoptera, Lepidoptera). Redtail samples contained more Lepidoptera taxa (p<0.05), while blue monkey samples contained more Araneae (p<0.05). Blue monkeys consumed a greater diversity of arthropod taxa than redtail monkeys (p<0.05); however, the average number of arthropod families present per fecal sample was greater in the redtail monkey samples (p<0.05). These results indicate that while overlap exists in the arthropod portion of their diets, 20-25% of taxa consumed are unique to each group. Our findings suggest that variation in arthropod intake may help decrease dietary niche overlap and hence facilitate coexistence of closely-related primate species.